One Health criteria to support decision-making on antimicrobial resistance interventions - Aluzaite, K.; Dione, Michel M.; Belay, D.; Robotham, J.V.; Guitian, J.; Chan, Derek; Emes, E.; Endalew, Y.G.; White, P.J.; Ramponi, F.; Knight, G.M. (World Organisation for Animal Health, 2025)
A One Health approach is widely recognised as key in addressing antimicrobial resistance (AMR) and is increasingly reflected in national action plans and global strategies. However, there is limited practical guidance on how to integrate a One Health perspective into the prioritisation and evaluation of AMR interventions to support decision-making. This article proposes a qualitative framework titled One Health Criteria to support decision-making on AMR interventions from a One Health perspective. It is based on assessment and characterisation of the setting where the intervention may be implemented, enabling early assessment of intervention impact according to outlined criteria (organised in themes and characteristics). It is a flexible, principle-based approach to guide AMR intervention planning and decision-making at all stages and levels, adaptable to diverse contexts. By enabling structured comparison of countries’ One Health profiles, the framework also promotes transferability and cross-learning for AMR intervention prioritisation. The authors identify three key themes that influence intervention success in a One Health perspective: i) ecosystem connectivity within and between sectors; ii) systemic societal factors, such as governance, policy and infrastructure; and iii) data availability to inform action. While this thematic approach supports early prioritisation, it is not a substitute for detailed analyses or economic evaluations where data permit. The authors aim to provide a practical tool for researchers and policy-makers to enhance the design and selection of AMR interventions within a One Health perspective. Future research should focus on refining the proposed themes and characteristics and developing robust methods to monitor and evaluate them.